(untitled) (Sebha University Conference Proceedings, 2025)
The study aimed to evaluate the effectiveness of using WhatsApp as an interactive educational platform at Wadi Al-Shati University. The research relied on a questionnaire to collect data, with a sample of 150 students. The questionnaire was divided into five groups: the first group included personal questions about gender and age; the second group included statements about academic interaction; the third group included statements about improving academic achievement; the fourth group included statements about developing educational skills; and the fifth group included statements about student satisfaction.